Teacher Transfers and Academic Performance of Learners in Uganda: A Case of Government Aided Primary Schools In Kalaki District. - Okello, George William (Kabale University, 2024)
This study aimed to examine the correlation between teacher transfers and learners’ academic performance in government aided primary schools in Kalaki District. The specific objectives of the study were to establish the relationship between voluntary transfers of teachers on learners' academic performance in government aided primary schools in Kalaki District the effects of routine transfers on learners' academic performance of government aided primary schools in Kalaki District and, the relationship between forced transfers on learners' academic performance in government aided primary schools in Kalaki District. The study adopted cross-sectional research design with the use of both quantitative and qualitative approaches. A sample size of 248 from a population of 369 respondents was selected to participate in the study. Both purposive and simple random sampling techniques were used in this study. Out of above sample size of 248, 195 respondents were able to fully take part in the study giving a response rate of 78.6%. The study established a significant positive relationship between voluntary transfers and academic performance of learners (r =0.640, p=0.000<0.000). The study also revealed a significant positive relationship between routine transfers and performance of teachers (r =-0.816, p=0.000<0.005). Further, the study indicated a significant positive relationship between forced transfers and performance of teachers (r=-0.814, p=0.000<0.005). The study concluded that: voluntary transfers, routine transfers and forced transfers enhance innovativeness of teachers as well as their performance. The study recommended that voluntary transfers should be used to enhance innovativeness of teachers for better performance. Routine transfer of teachers is generally a good policy in terms of performance and that the MOES is justified to transfer teachers who have overstayed. Forced transfers enhance innovativeness of learners especially if the teachers underperform and are therefore forced out of school.